Guest Editorial: Preface to "A Strange and Earnest Client" Part One of the Case of the Disappearing/Appearing Slow Learner: An Interpretive Mystery - W. John Williamson (University of Calgary, 2016)
Ladies and gentlemen, the story you are about to see is true. The names have been changed to protect the innocent (mytvmemories, 2012).